2018
DOI: 10.2174/1573403x14666180111145207
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Cardiac Remodeling: An Updated Edge

Abstract: Oxidative stress is considered a major stimulant for the signal transduction in cardiac cells pathological conditions, including inflammatory cytokines, and MAP kinase. The understanding of the pathophysiological mechanisms which are involved in cardiac hypertrophy and remodeling process is crucial for the development of new therapeutic plans, especially that the mortality rates related to cardiac remodeling/dysfunction remain high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 50 publications
2
71
0
Order By: Relevance
“…In addition to inflammation, obesity results in oxidative stress produced by excessive lipid peroxidation in mitochondria due to elevated glucose and lipid levels 30 . The accumulation of oxidative damage may contribute to cardiac inflammation and remodeling 31 but the induction of antioxidants HO-1 and NQO1 exert anti-oxidative and anti-inflammatory functions 32 . HO-1 confers protection against cardiac injury, and its catalytic by-products (biliverdin and carbon monoxide) have anti-hypertrophic effects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammation, obesity results in oxidative stress produced by excessive lipid peroxidation in mitochondria due to elevated glucose and lipid levels 30 . The accumulation of oxidative damage may contribute to cardiac inflammation and remodeling 31 but the induction of antioxidants HO-1 and NQO1 exert anti-oxidative and anti-inflammatory functions 32 . HO-1 confers protection against cardiac injury, and its catalytic by-products (biliverdin and carbon monoxide) have anti-hypertrophic effects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, dysfunctions of the various complexes of the mitochondrial respiratory chain are also observed in the non-infarcted zone of the myocardium in in vivo models of myocardial infarction, associated with a decrease in mitochondrial respiration [55]. These disruptions to the mitochondrial respiratory chain are associated with increased oxidative stress and ROS production, leading to the activation of many protein kinases and transcription factors involved in hypertrophic signaling [56] (Figure 4).…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Oxidative stress is closely related to cardiac hypertrophy and oxidative stress is considered to be a major inducer for the signal transduction in cardiac cells pathological conditions [28]. Thus, a large number of studies have shown that inhibition of oxidative stress can significantly prevent and improve cardiac hypertrophy [29][30][31].…”
Section: Discussionmentioning
confidence: 99%